Interleukin-6 Blockers Improve Inflammation-Induced Lipid Metabolism Impairments but Induce Liver Fibrosis in Collagen-Induced Arthritis - Denga, Tshimangadzo M.; Gunter, Sulè; Fourie, Serena; Roux, Regina l.; Manilall, Ashmeetha; Millen, Aletta M.E.; Mokotedi, Lebogang (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Interleukin-6 (IL-6) receptor blockers improve systemic inflammation, however, their inconsistent effects on lipid metabolism and drug-induced liver injuries warrant further investigation. This study aimed to determine the effects of IL-6 receptor blocker therapy on lipid metabolism and liver morphology in collagen-induced arthritis. Methods: Sixty three Sprague Dawley rats were divided into control (n = 24), inflammation (n = 24), and IL-6 blocker (n = 15) groups. Inflammation was induced in the inflammation and IL-6- blocker groups using Bovine type-II collagen and incomplete Freund’s adjuvant. At first signs of arthritis, the IL-6 blocker group received an IL-6 blocker, tocilizumab for six weeks. Serum concentrations of low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and ATP-binding cassette transporter-A1 (ABCA1) were measured. Liver fibrosis was determined by histological stains and liver enzymes were measured using the colorimetric-chemistry analyzer. Results: In the inflammation group, HDL-C and ABCA1 were reduced compared to control (p < 0.0001 and p = 0.04, respectively) and IL-6 blocker (p = 0.0003 and p < 0.0001, respectively) groups. LDL-C was increased in the inflammation compared to control (p = 0.02). Markers of liver fibrosis were increased in the IL-6 blocker group compared to control and inflammation groups (picrosirius red collagen area fraction: p < 0.0001 and p = 0.0008, respectively; Masson’s trichrome collagen area fraction: p = 0.0002 and p = 0.01, respectively). Alkaline phosphatase concentrations were increased in the IL-6 blocker group compared to the control (p < 0.0001) and inflammation (p = 0.002) groups. Conclusion: IL-6 blockers ameliorated inflammation-induced lipid metabolism impairments, however they induced liver fibrosis. Although IL-6 blockers may reduce inflammation-induced metabolic impairments in chronic inflammatory disorders, routine monitoring of liver function is warranted while on treatment.
Keywords: IL-6 receptor blocker